Training teachers to teach bioethics: evaluation using Kirkpatrick model - Piryani, Rano Mal; Piryani, Suneel; Bhandary, Shital (Journal of Patan Academy of Health Sciences, 2018)
Bioethics helps define the values and guidelines governing decision making in health profession practice. Teaching ethics to medical students demand teachers trained in bioethics. With this aim, “Teachers Training Workshop on Bioethics” was arranged with the objective to get feedback from the participants on effectiveness of bioethics teaching. Twelve faculty members participated in four days Teachers Training Workshop on Bioethics during Dec 27-30, 2016, at Patan Academy of Health Sciences, Nepal. Sixteen thematic topics were chosen from UNESCO Bioethics Core Curriculum. There were four rounds of presentations, and each round had four topics. Small group discussions, presentations and case scenarios were main methods used in the training. Written feedback was taken on semi-structured questionnaire with items- four closed ended and three open ended. Descriptive analysis was done. The level of confidence of the participants after participation in training workshop enhanced for teaching Bioethics, taking ethical decision and resolving ethical dilemma. As per participants open ended responses, “Active participation of the participants” and “Interactive sessions” were good points whereas “More references required, not only of UNESCO curriculum” was the area for improvement. The training enhanced overall confidence level of the participants.